3-tetrahydrofurfuryloxy-2-hydroxypropyl methacrylate: Synthesis, characterization, homopolymerization, and copolymerization - Coskun, M; Temuz, MM; Ahmedov, MA (Marcel Dekker Inc, 1996)
3-Tetrahydrofurfuryloxy-2-hydroxypropyl methacrylate monomer was prepared from methacrylic acid, tetrahydrofurfuryl alchol, and epichlorhydrin. Homopolymerization and copolymerization with (2-phenyl-1,3-dioxolane-4-yl)methyl methacrylate and N-vinyl pyrrolidone monomers were carried out in 1,4-dioxane solution at 60 degrees C using benzoyl peroxide as initiator. Infrared, proton and carbon-13 nuclear magnetic resonance techniques were used in characterizations of the monomer, the homopolymer and the copolymers were determined by DSC technique. The copolymer compositions were estimated from 1H-NMR spectra. The reactivity ratios in copolymerization of 3-tetrahydrofurfuryloxy-2-hydroxypropyl methacrylate and (2-phenyl-1,3-dioxolane-4-yl) methyl methacrylate were calculated by both Kelen-Tudos and Fineman-Ross methods.
Keywords: Tetrahydrofurfuryl Methacrylate; Reactivity Ratios; Polymerization; Membranes; System